Implementasi Pelayanan Penerbitan Surat Keterangan Catatan Kepolisian Polri: Studi Polres Payakumbuh - Utomo, Luhur Fachri; Kusumastuti, Retno (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
This research discusses the implementation of the police record certificate (SKCK) issuance service carried out at the Payakumbuh Police Station (Polres). SKCK is a form of service provided by the National Police (Polri) to the public in the form of a certificate containing police record data so that it can be used to fulfill objectives and fulfill an interest. This research uses a qualitative approach with data collection techniques through interviews, literature and document studies. The results of this research are that the implementation of SKCK issuance services at Payakumbuh Police (Polres) is already running, but is not yet optimal. Service implementation is influenced by resource factors, bureaucratic structure, disposition, and communication.